Correlation between intestinal stem cell niche changes and small bowel crypt failure in patients with treatment-naïve celiac disease - Prasenjit Das; Sudha Battu; Lalita Mehra; Alka Singh; Muzaffar Ahmad; Ashish Agarwal; Ashish Chauhan; Anam Ahmad; Sreenivas Vishnubhatla; Siddhartha Datta Gupta; Vineet Ahuja; Govind Makharia (Indian Journal of Pathology and Microbiology)
Objectives: We hypothesized that crypt failure in the small bowel results in villous flattening in patients with celiac disease (CeD). We investigated whether alterations in the stem cell niche (ISC) are responsible for this phenomenon. Materials and Methods: We included 92 duodenal (D2/3) biopsies from treatment-naive patients of CeD and 37 controls. All underwent screening for serum anti-tissue transglutaminase and endoscopic upper small bowel biopsy. Immunohistochemical markers were used to investigate ISC niche alterations, including LGR5 for crypt basal cells (CBC), Bmi1 for position 4+ cells, β-Defensin for Paneth cells, R-spondin1 as WNT activator, transcription factor-4 as WNT transcription factor, BMP receptor1A as WNT inhibitor, fibronectin-1 as periepithelial stromal cell marker, H2AX as apoptosis marker, and Ki67 as proliferation marker. We also analyzed IgA anti-tTG2 antibody deposits by using dual-color immunofluorescence staining. Results: We found that in biopsies from patients with treatment-naive CeD with modified Marsh grade 3a–3c changes, the epithelial H2AX apoptotic index was upregulated than in controls. LGR5+ crypt basal cells were upregulated in all modified Marsh grades compared to controls. However, the Ki67 proliferation index, expressions of WNT-activator RSPO1, and position-4 cell marker Bmi1 did not significantly alter in patients’ biopsies as compared to controls (P = 0.001). We also observed depletion of pericrypt stromal fibronectin-1 in patients with CeD compared to controls. In addition, we identified IgA anti-TG2 antibody deposits in pericrypt stroma. Conclusions: Our data suggests that ISC niche failure is a plausible hypothesis for villous flattening in patients with CeD, resulting from pericrypt IgA anti-TG2 antibody complex-mediated stromal depletion.